KONTRAK MURABAHAH PADA PRAKTIK LEMBAGA KEUANGAN SYARIAH DAN PROBLEMATIKANYA - Itona, Tuah (Universitas Muhammadiyah Surabaya, 2022)
Â Murabahah contracts are the most dominant transactions in financing contracts at Islamic Financial Institutions, because they are more consumptive in nature. The customer uses a murabahah contract with credit or installment financing by paying agreeing to the time defined in the initial contract agreement, but since the COVID-19 epidemic has commanded a biggish bump on the economy in the country, government, financial institutions, and the lower middle class especially those who have difficulty earning income and even employees who are laid off from their jobs. So that the financing agreement that was previously implemented becomes problematic because of bad credit financing. This study discusses how to deal with murabahah credit financing during the pandemic and how government policies minimize these problems. The breed of this exploration is archive exploration, the analysis applied in this research is qualitative and descriptive analysis, the data collection method uses the observation method. The results showed that in financing murabahah loans that were problematic during the pandemic, the government issued a policy through Financial Services Authority Regulation Number 48/POJK.03/2020 concerning Amendments to Financial Services Authority Regulation Number 11/POJK.03/2020 concerning National Economic Push as a Contracyclical Policy for the Impact of the Converlet of Corona Virus Disease 2019. In which there is one strategy by implementing credit restructuring or in this case financing as a rescue Try not to get worse and makes it difficult to resolve customer incompetence.